2023
DOI: 10.1002/oto2.27
|View full text |Cite
|
Sign up to set email alerts
|

Creation of an Open Bedside Tracheostomy Program at a Community Hospital With a Single Surgeon

Abstract: Objective To assess the adverse event rate and operating cost of open bedside tracheostomy (OBT) at a community hospital. To present a model for creating an OBT program at a community hospital with a single surgeon. Study Design Retrospective case series pilot study. Setting Academic‐affiliated community hospital. Methods Retrospective chart review of surgical OBT and operating room tracheostomy (ORT) at a communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Other studies also demonstrated positive outcomes while also showing that open methods can have less cost than percutaneous methods ( 8 , 9 ). In addition, a recent retrospective study showed open bedside tracheostomy in ICU had shorter operating times, similar complication rates and a crude cost saving of approximately $1900 compared to tracheostomy performed in theatre ( 10 ). Favourable outcomes were also demonstrated in another study with a lower cost compared to percutaneous dilatational tracheostomy ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also demonstrated positive outcomes while also showing that open methods can have less cost than percutaneous methods ( 8 , 9 ). In addition, a recent retrospective study showed open bedside tracheostomy in ICU had shorter operating times, similar complication rates and a crude cost saving of approximately $1900 compared to tracheostomy performed in theatre ( 10 ). Favourable outcomes were also demonstrated in another study with a lower cost compared to percutaneous dilatational tracheostomy ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pressing for "avoidance of high-risk sexual activity [as] championed by the otolaryngologist" can come across as patronizing and shaming, potentially straining the patientphysician relationship. Abstinence-only education falls short in practice, 2 and the disconnect here leads to adverse health outcomes. Connecting patients with resources for safe sexual practices may prove more effective than simply advising avoidance.…”
Section: Author Contributionsmentioning
confidence: 99%
“…As you nicely describe, this type of tracheostomy can be performed when safety concerns regarding transferring patients out of the intensive care unit, such as during the Covid 19 pandemic 1 . We have also described a protocol for performing bedside tracheostomies in many settings: a resource rich academic medical center, a public funded county hospital an"d a community‐based hospital with a single surgeon 2 . Thank you for highlighting training of the staff is vital to success but can be easily achieved.…”
mentioning
confidence: 99%